Model Pengembangan Community Based Tourism Desa Jangkaran, Kabupaten Kulon Progo - Daffa Hanief Wisnu Putranto, Daffa Hanief Wisnu Putranto; Rahayu Kistanti, Nurjannah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Community-based tourism (CBT) development grants broader authority to the community to manage their village's potential to enhance the economy and sustainable development. This study aims to find a model for community-based tourism (CBT) development in Jangkaran Village, Kulon Progo, Yogyakarta, which has the potential for ecotourism, cultural tourism, and agrotourism. The research employs a mixed-methods approach, combining qualitative and quantitative methods, collecting data through observation, interviews, Focus Group Discussions (FGD), and documentation, with the aid of SWOT analysis to determine priority strategies for tourism development in integration with the CBT model. The results show that community participation in managing tourist attractions is quite good, with most mangrove tourism attractions managed by Jangkaran community groups, and the presence of creative economy elements such as local art events, culinary offerings, and unique souvenirs. The challenges faced by Jangkaran tourism stakeholders include development programs and the construction of attractions, amenities, and accessibility, which are still hindered by regulations that do not fully support Jangkaran's tourism development. Based on the SWOT IFAS-EFAS analysis, the strategic position for Jangkaran Village tourism development falls into the SO (Strengths-Opportunities) quadrant, indicating a Competitive Strategy. Gradually, this CBT model can be applied in Jangkaran Village through an institutional collaboration approach, thereby realizing sustainable tourism, creating job opportunities for Jangkaran residents, and strengthening the village and household economy. This study can serve as a guide for Jangkaran Village to further develop tourism direction through careful planning, prioritizing sustainable development principles, and emphasizing community participation in planning, implementation, monitoring, and evaluation.